PM10 PREDICTION OF INDUSTRIAL AREAS FOR NEW AIR QUALITY STANDARD - NAZIF, AMINA NASIR (2017)
Particles with an aerodynamic diameter of :::;1 0 f.lg/m3 (PMw) are air pollutants that have resulted in tremendous health effect to the exposed populace. Hence, a new National Ambient Air Quality Standard (NAAQS) is presented in Malaysia.